PERAN KEPEMIMPINAN DALAM MENUMBUHKAN N/ACH - Elysabet .; Sugeng Rusmiwari (Universitas Tribhuwana Tunggadewi, 2019)
Abstract: Leadership (leadership) is an important issue in the phenomenon of organizational society. The phenomenon of leadership in an organization can determine the targets to be achieved, because leaders are core factors that have the legitimate power to influence others in a certain way. This type of research uses a quantitative approach with descriptive study method, which is a method directed to solve problems by describing or explaining the results of research as it is. Steps of data collection by using questionnaires or closed questions, data taken from the population is the element of leadership or head with Purposive Sampling technique (sample aims). The result, leadership has a tendency of 38% good, achievement motivation has a tendency of 31% good. Leaders have a role of 61% can grow achievement motivation (n / Ach) of 46%. Keywords: Leadership, Achievement Motiv Abstrak: Kepemimpinan (leadership) merupakan isu penting dalam fenomena masyarakat organisasi. Fenomena tentang kepemimpinan dalam sebuah organisasi dapat menentukan target yang hendak dicapai, karena pemimpin merupakan faktor inti yang memiliki kekuasaan sah untuk mempengaruhi orang lain dengan cara tertentu. Jenis penelitian ini menggunakan pendekatan kuantitatif dengan metode studi deskriptif, yaitu metode yang diarahkan untuk memecahkan masalah dengan cara menggambarkan atau memaparkan hasil penelitian apa adanya. Langkah-langkah pengumpulan data dengan menggunakan kuesioner atau pertanyaan tertutup, data diambil dari populasi yaitu unsur pimpinan atau kepala dengan teknik Purposive Sampling (sampel bertujuan). Hasilnya, kepemimpinan memiliki kecenderungan sebesar 38% baik, motiv berprestasi memiliki kecenderungan sebesar 31% baik. Pemimpin memiliki peranan sebesar 61% dapat menumbuhkan motiv berprestasi (n/Ach) sebesar 46%. Kata kunci: Kepemimpinan, Motiv Berprestasi